2020
DOI: 10.1007/s41030-020-00123-8
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin for Antibiotic Prescription in Chronic Obstructive Pulmonary Disease Exacerbations: Systematic Review, Meta-Analysis, and Clinical Perspective

Abstract: The 2020 Global Initiative for Obstructive Lung Disease report indicates that the blood biomarker procalcitonin (PCT) may assist in decision-making regarding the initiation of antibiotics for chronic obstructive pulmonary Digital Features To view digital features for this article, go to https://doi.org/10.6084/m9.figshare. 12582098.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Another meta-analysis from 2017 with a slightly different selection of trials also found a significant reduction of antibiotic exposure without a significant effect on mortality, length of stay (LOS), or treatment failure [ 28 ]. The significantly lower use of antibiotics was further confirmed by a meta-analysis conducted in 2020, which included trials until 2018 [ 71 ]. However, the authors did not support the use of PCT-guided therapy for ECOPD as the effect on antibiotic duration disappeared when trials with a high risk for bias were excluded [ 71 ].…”
Section: Medical Wardmentioning
confidence: 96%
See 1 more Smart Citation
“…Another meta-analysis from 2017 with a slightly different selection of trials also found a significant reduction of antibiotic exposure without a significant effect on mortality, length of stay (LOS), or treatment failure [ 28 ]. The significantly lower use of antibiotics was further confirmed by a meta-analysis conducted in 2020, which included trials until 2018 [ 71 ]. However, the authors did not support the use of PCT-guided therapy for ECOPD as the effect on antibiotic duration disappeared when trials with a high risk for bias were excluded [ 71 ].…”
Section: Medical Wardmentioning
confidence: 96%
“…The significantly lower use of antibiotics was further confirmed by a meta-analysis conducted in 2020, which included trials until 2018 [ 71 ]. However, the authors did not support the use of PCT-guided therapy for ECOPD as the effect on antibiotic duration disappeared when trials with a high risk for bias were excluded [ 71 ]. Thus, despite the general agreement that PCT-guided therapy can reduce antibiotic use, the quality, bias, and heterogeneity of the available evidence are insufficient and further research is needed, particularly for determining optimal cutoff values or comparing PCT to CRP [ 26–28 , 72 ].…”
Section: Medical Wardmentioning
confidence: 96%
“…Procalcitonin has also been regarded as a useful biomarker in guiding antibiotic therapy. However, a recent meta-analysis contradicted these results 110 and therefore further investigation is warranted.…”
Section: Treatable Traits Applied To Copd Exacerbationsmentioning
confidence: 95%
“…Personalizing COPD exacerbation therapy may be aided by biomarker‐guided therapy. A meta‐analysis found that the use of procalcitonin (PCT) to guide antibiotic prescription in hospitalized AECOPD was associated with a reduced duration of antibiotic use (−2.1 (−3.89 to −0.14) days, P = 0.04) but did not reduce length of hospitalization, treatment failure, readmission or mortality 40 . Of note, intensive care unit stay was longer when managed with PCT‐based protocols (4 (0.74–7.32) days, P = 0.02).…”
Section: New Developments In Copdmentioning
confidence: 99%